1979
DOI: 10.1152/jappl.1979.47.4.792
|View full text |Cite
|
Sign up to set email alerts
|

Increased lung lymph transport without heart failure after coronary ligation in sheep

Abstract: Pulmonary edema frequently accompanies acute myocardial infarction (MI). We measured pulmonary arterial (PAP), left atrial (LAP), and aortic pressures (AP),lung lymph flow (QL), and clearance of total serum protein and each of eight protein fractions in five anesthetized sheep before and after coronary artery ligation. After a stable base line of 1 h, ligation produced significant increases in LAP, QL, and clearance of total protein and four protein fractions, but no significant changes in PAP, AP, or lymph-to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1981
1981
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Dogs after coronary ligation have higher gravimetric lung water than control dogs with comparable P mv (Spath and Gee, 1979). Lung lymph flow and pulmonary protein clearance in anesthetized sheep rises shortly after coronary ligation despite minimal change in P mv (Collins et al, 1979).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Dogs after coronary ligation have higher gravimetric lung water than control dogs with comparable P mv (Spath and Gee, 1979). Lung lymph flow and pulmonary protein clearance in anesthetized sheep rises shortly after coronary ligation despite minimal change in P mv (Collins et al, 1979).…”
Section: Discussionmentioning
confidence: 94%
“…Although several laboratories have reported similar conclusions using different methods (Massion et al, 1976;Gee et al, 1978;Collins et al, 1979), the mediator(s) of this rise in permeability has not been identified. Berger and co-workers (1976) have shown that after coronary ligation in the anesthetized dog, there is release of prostaglandins E and F from the ischemic myocardiium.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…During reperfusion, specific myocardial enzymes (presumably leaked from damaged or necrotic tissue) and inflammatory cytokines 14 are being washed out and reach the lungs, 15 which might lead to lung injury. A series of acute experimental studies 5,[16][17][18] has demonstrated that coronary artery occlusion and reperfusion resulted in pulmonary edema, evidenced by an increase in extra-vascular lung water. Increased pulmonary microvascular permeability is suggested as one of the possible mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…the possible neurogenic component to HAPE, 14 as both cerebral and pulmonary edema of high altitude may coexist; 39 3. the possible role of endogenous opiatesas naloxone, the opiate receptor antagonist, prevents the increased lung lymph flow secondary to intracranial hypertension in sheep; 31 and 4. myocardial ischemia without overt heart failure. 6 With this continued search for mechanism(s) causing HAPE comes the hope that the prevention and cure for the condition will also be found. Nevertheless, it still seems likely that cautious ascent to altitude will remain the best preventative measure and rapid descent once HAPE develops, the best cure.…”
Section: Platelets and Hapementioning
confidence: 99%